ANALISIS PARTISIPASI MASYARAKAT DALAM PENGELOLAAN EKOWISATA PANTAI CLUNGUP MANGROVE CONSERVATION (CMC) - harahab, nuddin; Riniwati, Harsuko (JFMR (Journal of Fisheries and Marine Research), 2020)
Coastal ecotourism is a coastal tourism activity developed with a conservation approach and utilizing the characteristics of coastal resources as a tourist destination. The purpose of this study is to analyze the factors that determine community participation in ecotourism management at CMC. Data analysis methods use descriptive analytics, this method is used to describe data that has been obtained through analytic processes which are then presented in the form of language or narrative. Data from observations and interviews were analyzed using conservation principles. The results of the study indicate that the driving factor for the creation of participation is the presence of economic incentives or income opportunities. While the level of community participation in CMC ecotourism management is still low and needs to be improved.